2002
DOI: 10.1093/humrep/17.8.2085
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection and assisted reproduction

Abstract: Since the risk for vertical and laboratory HCV infection is not well determined, and HCV prevalence is not negligible in this group, we recommend that infertile patients be screened before assisted reproductive techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
1
8
0
3
Order By: Relevance
“…The authors concluded that sexual transmission plays an important role in the propagation of HCV infection in humans. PASSOS et al (2002) 62 concluded that sexual and perinatal transmission was low among 409 patients from an assisted reproduction clinic. In 1995, FIGUEIREDO et al 22 analyzed 83 couples, and the incidence of 2.4% in this group suggested sexual transmission.…”
Section: Souto Et Al (1994)mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that sexual transmission plays an important role in the propagation of HCV infection in humans. PASSOS et al (2002) 62 concluded that sexual and perinatal transmission was low among 409 patients from an assisted reproduction clinic. In 1995, FIGUEIREDO et al 22 analyzed 83 couples, and the incidence of 2.4% in this group suggested sexual transmission.…”
Section: Souto Et Al (1994)mentioning
confidence: 99%
“…In 1995, FIGUEIREDO et al 22 analyzed 83 couples, and the incidence of 2.4% in this group suggested sexual transmission. The authors considered this route to be probable but not very efficient 22,50,62,88 .…”
Section: Souto Et Al (1994)mentioning
confidence: 99%
“…La transmisió n de la infecció n ocurre principalmente mediante la vía parenteral, aunque tambié n se puede dar por contacto sexual y transmisió n vertical. Si bien aú n no se ha calculado el riesgo exacto de una posible transmisió n vertical madre-hijo, se ha observado en mujeres con altos niveles de viremia la capacidad de infectar a su descendencia 34 y se ha reportado que mujeres co-infectadas con VHC y VIH-1 tienen un mayor incremento en las posibilidades de transmitir la hepatitis C a sus hijos 35 . Cerca de 150-180 millones de personas en el mundo son portadoras de la enfermedad y hasta el momento solamente se ha reportado una tasa del 5% de transmisió n de la infecció n por vía sexual y vertical 36 .…”
Section: Virus De La Hepatitis Cunclassified
“…Ante tanta polé mica, se ha concluido que el virus se encuentra presente en semen en bajas o en indetectables concentraciones, dependiendo de la metodología empleada para la detecció n, lo que no representaría un riesgo alto de transmisió n sexual, pero sí podría contribuir a la infertilidad masculina a causa de reacciones inmunoló gicas e inflamatorias 35 .…”
Section: Virus De La Hepatitis Cunclassified
“…The risk of hepatitis C transmission in assisted reproduction techniques is currently the subject of widespread debate 11,22,33 . LEVY et al investigated the presence of HCV RNA in the semen of infected men in order to find out if semen fractions act as a reservoir for the hepatitis C virus.…”
Section: Introductionmentioning
confidence: 99%